Optimization of Protoplast Preparation and Establishment of Genetic Transformation System of an Arctic-Derived Fungus Eutypella sp. - Ning, Yaodong; Hu, Bo; Yu, Haobing; Liu, Xiaoyu; Jiao, Binghua; Lu, Xiaoling (Frontiers in Microbiology, 2022)
Arctic-derived fungus Eutypella sp. D-1 has attracted wide attention due to its huge ability to synthesize secondary metabolites. However, current studies only focus on stimulating its production of new secondary metabolites by OSMAC strategies, and the relationship between secondary metabolites and biosynthetic gene clusters has not been explored. In this study, the preparation and regeneration conditions of Eutypella sp. D-1 protoplasts were explored to lay a foundation for the study of genetic transformation of this fungus. Orthogonal experiment showed that the optimal preparation conditions were 0.75 M NaCl, 20 g/ L Lysing enzyme and 20 g/ L Driselase, 28 ℃ for 6 hours. The maximum yield of Eutypella sp. D-1 protoplasts could reach 6.15×10^6 cells·mL-1, and the concentration of osmotic stabilizer NaCl was the most important factor for Eutypella sp. D-1 protoplasts. The results of FDA staining showed that the prepared protoplasts had good activity. Besides, the best protoplasts regeneration medium was YEPS, whose maximum regeneration rate is 36%. The mediums with nitrogen sources such as SR and RM also had good effects on the Eutypella sp. D-1 protoplasts regeneration, indicating that nitrogen sources played an important role on the Eutypella sp. D-1 protoplasts regeneration. Subsequent transformation experiments showed that hygromycin resistance genes could be successfully transferred into the genome of Eutypella sp. D-1, indicating that the prepared protoplasts could meet the needs of subsequent gene manipulation and research. This study lays a foundation for the genetic transformation of Eutypella sp. D-1.